Effects of aflatoxin B, on the erytrocytes, liver, kidney arginase activities and serum ALP, AST, ALT In’els of rabbits (Annals of Medical Research, 2021)
None
Keywords: AJlatoxin Bi , arginase activity, serum ALP, AST and ALT levels.